In between subjects a critical genealogy of queer performance - Jones, Amelia 1961- (Routledge, Taylor & Francis Group, 2021)
Performativity -- Relationality -- Theatricality -- Queer -- Other -- Trans
Includes bibliographical references and index
Keywords: Homosexuality and the arts; Performative (Philosophy); Sex role in art